The Coaching Maps as a Tool for Developing Reflectivity in Organisations - Marta Geisler; Robert Geisler (Problemy Zarządzania, 2019)
Our view of organizations, labour and the competencies of managers will soon need to change. In the postmodern and post-Fordist world, economy and organizations function differently than they did in the 20th century. Workers and managers will have to face new expectations. Not only has reflectivity become one of the key organisational factors; it is also taught, learnt and shaped. Drawing on an authoethnographic model and action-research, authors of this paper provide an education and development tool that managers and workers can use to develop and trigger reflectivity. Picture ethnography, coaching philosophy and hermeneutics are theoretical bases for the construction of a new model of self-development.